THE INFLUENCE OF DIGITAL MARKETING AND LIFESTYLE ON THE DECISIONS OF E-COMMERCE (SHOPEE) USERS IN INDUSTRY 4.0 - Rido Dwi Kurniawan Kurniawan; Richardus Eko Indrajit (Informatika, Universitas Jenderal Soedirman, 2022)
The industrial revolution is a fundamental change in the way of life and human work processes, where advances in information technology can integrate the life of the digital world. The right digital marketing and still paying attention to the lifestyle of every community is a success in achieving the desired marketing target, including in the world of the trade industry where various innovations continue to emerge. This study aims to determine the effect of Digital Marketing and Lifestyle on the Decisions of E-Commerce Users (Shopee) in Industry 4.0. This research was conducted with a quantitative research design where the data source is secondary data in the form of E-Commerce user data. Data were collected through questionnaires and analyzed by multiple linear regression with classical assumptions, namely Normality Test, Multicollinearity Test, Heteroscedasticity Test. The capital feasibility test is the coefficient of determination, F test and t test. Based on the results of the classical assumption test, it shows that Digital Marketing and Lifestyle have a positive and significant effect on the dependent variable on the decisions of E-Commerce users at Shopee. By using a multiple regression analysis system, the results show that Digital Marketing and Lifestyle have a partial effect on the decisions of E-Commerce users with the Digital Marketing variable value tcount 1,988 > ttable 1.660 and tcount Lifestyle tcount 2.479 > ttable 1.660. The results showed that the Digital Marketing and Lifestyle variables simultaneously had a positive effect on the decisions of E-Commerce users by 1.3% and 98.7% with a 95% confidence level explained by other variables outside the study.